Monte Carlo simulation of light distribution on the biological tissue surface by the factors of light source and internal target - Ma, Jing (2018)
In the recent years, optical imaging has attracted increasing attention in the field of clinical diagnosis and therapy due to the non-invasive nature. This project aims to study a forward problem in tissue optics to investigate the effect of the light source and internal target (e.g. the size and position) on the light distribution (e.g. diffuse reflectance, fluorescence reflectance) collected from the turbid biologic tissue based on the Monte Carlo simulation platform, e.g. MOSE, MCML-Fluor and MCML-EO. This study could help to create a sharp focus in a highly scattering tissue sample for optical imaging as well as to obtain the valuable information from biological tissues with cancerous tumors and lesion. In addition to the total fluorescence or diffuse reflectance, in MCML-based program both the radius and angular profile of the light distribution are studied and compared across a range of the testing parameters. And the angular profile of the light distribution shows a potential to distinguish the tissue with and without the tumor/lesion due to the large discrepancy exhibited as compared to the radius profile.